FRGS15-192-0433: Identifying the minimum invasive active fire protection measures for Malaysian heritage buildings towards better preservation of the built heritage - Salleh, Nurul Hamiruddin (2018)
In the case of a heritage building, until today, no proper legal requirements have been endorsed to protect historic contents and structures from fire. According to many international fire experts, fire safety systems in heritage buildings must be sympathetically designed in order to minimise the impact on the historic character (authenticity) of the buildings. Nevertheless, although many lessons have been learned and approaches to fire safety in heritage buildings have grown more sophisticated, one simple fact remains: most fires occur as a result of human action or negligence. Special considerations should be applied in upgrading fire safety systems in heritage buildings. Not only must the systems aim to comply with the relevant standards and provide the intended levels of protection, but additionally their impact on the building and its fabric must meet a range of tests. Furthermore, it is essential that full consideration be paid to the risks of potential damage to original fabric as well as the aesthetic impact fire systems might have on heritage buildings. Any changes to a listed building must not only address fire protection needs but must fully comply with the law in respect of listed building consent. The main objective of this study is to identify and evaluate active fire protection (AFP) measures in heritage buildings that able to provide an acceptable level of safety for both people and property with minimum invasive into the historic fabrics. Other than literature reviews, a series of observations, interviews with fire experts and case studies will be employed to provide primary data in this study. At the end of the study, a practice guidance in selection and installation of active fire protection measures in Malaysian heritage buildings has been recommended.